2023
DOI: 10.1007/s00404-023-07075-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating compliance and applicability of postpartum pessary use for preventing and treating pelvic floor dysfunction: a prospective multicenter study

Abstract: Purpose Pelvic floor disorders are common and associated with pregnancy and childbirth. For restitution of pelvic floor connective tissue and thereby therapy of postpartum pelvic organ prolapse and stress urinary incontinence, the Restifem® pessary is approved. It supports the anterior vaginal wall behind the symphysis, the lateral sulci and the sacro-uterine ligaments and stabilises the connective tissue. We evaluated the compliance and applicability of Restifem® use in women postpartum in a pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Pessary and RF were found to have little effect on enhancing the contraction force of muscle fibers. They mainly play a physical support and fascia regeneration role in the treatment of cystocele, rather than playing a role by enhancing pelvic floor muscle strength ( 25 , 26 ). In fact, the results in this study showed that the 3 treatments improve cystocele through different mechanisms; this discrepancy prompts further exploration into the underlying mechanisms and factors influencing these distinct treatment outcomes, and it will be beneficial for the clinical significance or potential consequences of patient outcomes and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Pessary and RF were found to have little effect on enhancing the contraction force of muscle fibers. They mainly play a physical support and fascia regeneration role in the treatment of cystocele, rather than playing a role by enhancing pelvic floor muscle strength ( 25 , 26 ). In fact, the results in this study showed that the 3 treatments improve cystocele through different mechanisms; this discrepancy prompts further exploration into the underlying mechanisms and factors influencing these distinct treatment outcomes, and it will be beneficial for the clinical significance or potential consequences of patient outcomes and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, vaginal pessaries were more effective than standard care or PFMT to treat postpartum urinary incontinence. Only a few studies have investigated the use of vaginal pessaries to treat urinary incontinence, and only one other study studied vaginal pessaries as a treatment for postpartum women 14 18 23 24 . A Cochrane analysis from 2014 found insufficient evidence to recommend vaginal pessaries over PFMT for treating UI due to the lack of data 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Only very few studies have investigated the use of pessaries for postpartum women. Recently, one prospective cohort study studied the compliance with the Restifem pessary 18 . 71% of the pessary users still used the pessary after 3 months but no comparison with other treatments was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Pessaries and other vaginal inserts for SUI are additional well tolerated options for pregnant and postpartum patients. Postpartum-specific pessaries have shown improvement in urinary incontinence symptoms at both 3 and 6-month postpartum [32]. Specific postpartum pessaries such as the Restifem have been utilized as early as 6 weeks postpartum [32].…”
Section: Management Of Postpartum Urinary Incontinencementioning
confidence: 99%
“…Postpartum-specific pessaries have shown improvement in urinary incontinence symptoms at both 3 and 6-month postpartum [32]. Specific postpartum pessaries such as the Restifem have been utilized as early as 6 weeks postpartum [32]. However, earlier use in a symptomatic patient could be considered for patients with minimal or no vaginal tearing from the obstetric delivery (including cesarean section) and would be at the discretion of the obstetric provider.…”
Section: Management Of Postpartum Urinary Incontinencementioning
confidence: 99%